Nursing leadership and its organizational impact in the hospital. Bibliographic review - Carrasco Valdez, Jennifer Dayana; Heredia Nugra, Soraya Margoth (Enfermería Cuidándote, 2026)
Introduction: Nursing leadership is defined as the ability of nursing staff to influence, direct and organize teams within the hospital environment, facilitating effective communication and cultivating a constructive work environment. This form of leadership encompasses competencies such as empathy, conflict resolution and strategic decision making.Objective: To evaluate the influence of nursing leadership and its organizational impact in the hospital setting through a systematic review.Methodology: A literature review was conducted following specific inclusion and exclusion criteria. The search included academic databases such as PubMed, Scielo, Semantic, Dialnet, and Google Scholar. Under the guidelines of the PRISMA Diagram, 19 relevant studies were included. The data were classified into three main categories: leadership styles, leadership characteristics and leadership impact.Results: The analysis revealed that transformational and transactional leadership styles are positively correlated with job satisfaction, mutual trust and the practice of a safety culture. In addition, specific leadership development programs were shown to enhance the competencies of nursing leaders.Conclusions: Leadership effectiveness in nursing has a beneficial effect on organizational performance, particularly with regard to job satisfaction and patient safety. However, methodological and contextual limitations have been identified, highlighting the need for longitudinal research.
Keywords: Health Management; Hospital Administration; Leadership; Nursing